Challenges faced by undergraduate dental students during root canal treatment: a survey study - Gurdeep SINGH; Abubaker QUTIESHAT; Ahmad AL WAHAIBI (Universidade Estadual Paulista, 2023)
Abstract Introduction root canal treatment is a challenging procedure often first encountered by undergraduate dental students, leading to various difficulties and mistakes. Objective this study aimed to identify the specific difficulties encountered by undergraduate dental students during root canal treatment and the frequency of mistakes they committed in relation to these difficulties. Material and method this study employed a cross-sectional survey design. A cohort of 60 third-year students completed a self-administered questionnaire consisting of 27 questions addressing various aspects of endodontic treatment and 11 key areas of root canal procedures. The response options for each question were based on a 4-point Likert scale. Data analysis was performed using Python programming language and heatmaps were created using the seaborn library to better understand the distribution of the data. Result students encounter challenges in developing tactile sensation, accessory cone placement, and accurately reaching the apex during canal location. Dental schools should focus on improving students' tactile skills and methods to reach the apex to enhance the effectiveness of root canal treatment education. In contrast, students reported fewer mistakes in rubber dam application and safety measures during treatment. Dental educators should emphasize proper instrument use and safety precautions during root canal treatment. Interestingly, students did not perceive these areas as problematic despite committing mistakes. Conclusion this study provides valuable insights into the challenges and mistakes encountered by undergraduate dental students during root canal treatment. Dental educators should address these issues to improve students' skills and techniques and provide optimal patient care.